The practice of her profession : Florence Carlyle, Canadian painter in the age of impressionism - Butlin, Susan (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history, 2009)
""CONTENTS""; ""ILLUSTRATIONS""; ""ACKNOWLEDGMENTS""; ""INTRODUCTION""; ""PLATES""; ""PREAMBLE""; ""PART ONE: FORMATION, 1864â€?1890""; ""1 First Lessons, 1864â€?1883""; ""2 Contacts, 1883â€?1890""; ""PART TWO: EMERGENCE, 1890â€?1899""; ""3 The Bohemia of Paris, 1890â€?1896""; ""4 Brass and Copper: Alternatives and Strategies, 1896â€?1899""; ""PART THREE: A LIFE APART FROM CONVENTION, 1899â€?1914""; ""5 The Village, 1899â€?1903""; ""6 Acclaim, 1903â€?1911""; ""7 Losses and Gains, 1911â€?1914""; ""PART FOUR: OUT OF THE MAINSTREAM, 1915â€?1923""; ""8 Resolutions, 1915â€?1923""